A preparation method of a high-molecular material resistant to radiation, high temperature and high pressure
Patent Information
- Application Number
- CN202611239432.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-09-18
AI Technical Summary
[0005]本发明目的之一在于提供一种用于耐辐照、耐高温和承高压的高分子材料,以解决现有技术中多孔无机填料与高分子基体仅形成物理接触、高分子链不能有效进入填料孔道、持续高压下界面链段容易滑移并产生压缩蠕变的问题
[0017] 1. The hafnium-oxygen cluster nodes of this invention have high atomic numbers, and the porphyrin ligands used... Aromatic polyimides, in particular, contain conjugated structures, allowing excited-state electrons and free radicals generated by irradiation to undergo local transfer, delocalization, or trapping between these structures; confined within the channels
Concentrated near the interface between the metal nodes and the polymer, it can reduce
Aggregation and migration within the continuous phase increase the probability of contact with radiation-active species, preventing free radicals from further initiating chain breakage of the polymer backbone; simultaneously, activation of the hafnium-porphyrin metal-organic framework and
The pores are loaded and combined with low-molecular-weight diamines to enter the remaining pores and undergo in-situ polycondensation. This avoids the problem that pre-made polymers mainly remain on the outer surface of particles due to their large molecular size and system viscosity. This forms a through-and mechanical interlocking effect between the polyimide inside and outside the pores and the metal-organic framework. The polymer inside the pores provides support for the porous framework, while the rigid framework restricts the polymer chain segments from sliding under continuous pressure, reducing the tendency for compression creep, interfacial debonding, and microcrack formation.
Smart Images

Figure CN122772364A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials resistant to extreme environments, and more particularly to a method for preparing polymer materials that are resistant to radiation, high temperatures, and high pressures. Background Technology
[0002] The sealing components inside a nuclear reactor are subjected to high temperature and high pressure environments for extended periods, as well as various forms of nuclear radiation such as gamma rays and neutron flux. Conventional rubber, fluoropolymers, or ordinary thermoplastic polymers are highly susceptible to chain segment relaxation, thermo-oxidative degradation, and permanent compression deformation under such conditions. Furthermore, during the irradiation process, the polymer backbone may undergo ionization, excitation, chain breakage, or disordered cross-linking, generating active free radicals that trigger chain degradation, thereby reducing the material's strength, toughness, and sealing stability.
[0003] Existing radiation-resistant polymer materials are typically modified by increasing the aromatic content, adding inorganic particles, heavy metal oxides, antioxidants, or free radical scavengers. However, the contact between ordinary inorganic fillers and the polymer matrix is mainly physical, resulting in limited interfacial wettability and load transfer capacity. Furthermore, particle agglomeration and interfacial voids can increase local stress concentration. Currently, porous metal-organic frameworks (MOFs) have strong application prospects due to their rigid framework and tunable pores. However, current technologies still rely on simple physical blending, making it difficult for polymer chains to enter the pores of MOFs. The pores of MOFs may still shrink under high pressure, failing to effectively restrict chain slippage. Simultaneously, free and dispersed hindered phenols or fullerenes are prone to agglomeration, migration, or loss from the interfacial region, making it difficult for them to function continuously at the sites of radiation-induced free radical generation.
[0004] In other words, simply increasing the content of fillers or free radical scavengers cannot simultaneously improve pressure resistance, heat resistance, and radiation resistance. Therefore, there is an urgent need to establish a method for preparing polymer materials with defined component ratios, pore loading sequences, in-situ polymerization pathways, and interfacial coordination structures, so that the rigid framework, free radical scavenging units, and aromatic polymer continuous phases can form stable connections at the molecular and nanoscale. Summary of the Invention
[0005] One of the objectives of this invention is to provide a polymer material that is resistant to radiation, high temperature, and high pressure, in order to solve the problems in the prior art where porous inorganic fillers only form physical contact with the polymer matrix, polymer chains cannot effectively enter the filler pores, and interface chain segments are prone to slippage and compression creep under continuous high pressure.
[0006] This invention is achieved through the following technical solution: a method for preparing a polymer material that is radiation-resistant, high-temperature resistant, and high-pressure resistant, comprising the following steps: an aromatic polyimide matrix as the continuous phase, and fullerene-supported hafnium-porphyrin metal-organic framework particles dispersed in the aromatic polyimide matrix; the hafnium-porphyrin metal-organic framework particles are porous crystalline materials formed by the coordination of hafnium-oxygen cluster nodes with carboxyl-containing porphyrin ligands, and the porous crystalline material has mesopores. The fullerene is confined within the mesoporous channels and open hafnium coordination sites; the aromatic polyimide matrix is a product obtained by imidization reaction of an aromatic dianhydride component and an aromatic diamine component, the aromatic diamine component including an aromatic diamine containing a pyridine structure, the pyridine nitrogen in the aromatic diamine containing the pyridine structure being coordinated with the open hafnium coordination sites, thereby forming an interfacial coordination bond between the hafnium-porphyrin metal-organic framework particles and the aromatic polyimide matrix.
[0007] Furthermore, the hafnium-porphyrin metal-organic framework particles are PCN-222 type metal-organic frameworks, the hafnium oxygen cluster nodes are nodes containing Hf6O4(OH)4 clusters, and the carboxyl-containing porphyrin ligand is tetrakis(4-carboxyphenyl)porphyrin.
[0008] Furthermore, the fullerene is a fullerene. .
[0009] Furthermore, the hafnium-porphyrin metal-organic framework particles have an open hafnium coordination site content of 0.15~0.80 mmol / g, a mesopore size of 3.0~4.0 nm, and a median particle size D50 of 100~460 nm; the aromatic dianhydride component is 3,3′,4,4′-biphenyltetracarboxylic dianhydride, and the molar ratio of the aromatic dianhydride component to the aromatic diamine component is 0.98:1~1.02:1.
[0010] Furthermore, based on 100 parts by weight of the aromatic polyimide matrix, the content of the fullerene-supported hafnium-porphyrin metal-organic framework particles is 8 to 25 parts by weight, and the proportion of fullerene in the hafnium-porphyrin metal-organic framework particles is 2 to 10 wt%.
[0011] Furthermore, the proportion of extractable surface fullerenes in the fullerene-supported hafnium-porphyrin metal-organic framework particles is no more than 20 wt%, and the residual chlorine content is no more than 100 mg / kg.
[0012] Another aspect of the present invention provides a method for preparing a polymeric material that is radiation-resistant, high-temperature resistant, and high-pressure resistant. The polymeric material described above is prepared according to the following method: S1, activating hafnium-porphyrin metal-organic framework particles; S2, fullerene channel loading: adding the activated hafnium-porphyrin metal-organic framework particles to a fullerene solution, and subjecting the solution to a depressurization-repressurization cycle to allow the fullerene to enter and be confined within the mesoporous channels, followed by separation, washing, and drying to obtain fullerene channel-loaded hafnium-porphyrin metal-organic framework particles; S3. In-situ formation of polyamic acid: The aromatic diamine component, including an aromatic diamine containing a pyridine structure, is dissolved in an organic solvent, added to the particles obtained in S2 and dispersed. The diamine solution is then allowed to enter the remaining channels of the mesoporous channels through a depressurization-repressurization cycle. Subsequently, the aromatic dianhydride component is added in batches to react and obtain a composite polyamic acid system. S4. Segmented imidization: The composite polyamic acid system is degassed, molded, and imidized by programmed temperature rise. Pressure is applied during the high-temperature stage of imidization, and the pressure is maintained before cooling to obtain the polymer material.
[0013] Furthermore, the activation described in S1 is carried out at a temperature of 120~180 ℃ and an absolute pressure of 50~500 Pa; the solvent of the fullerene solution in S2 is o-dichlorobenzene, chlorobenzene or a mixture of the two, and the number of depressurization-repressurization cycles is 2~6 times.
[0014] Furthermore, the highest temperature of imidization in S4 is 260~330 °C, and the pressure applied during the high-temperature stage is 5~30 MPa.
[0015] Furthermore, the preparation method also includes: S5, curing the polymer material obtained in S4 at 340~360 ℃ under an inert atmosphere, then pretreating it in deoxygenated water at 280~320 ℃ and 10~18 MPa, and then drying it.
[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0017] 1. The hafnium-oxygen cluster nodes of this invention have high atomic numbers, and the porphyrin ligands used... Aromatic polyimides, in particular, contain conjugated structures, allowing excited-state electrons and free radicals generated by irradiation to undergo local transfer, delocalization, or trapping between these structures; confined within the channels Concentrated near the interface between the metal nodes and the polymer, it can reduce Aggregation and migration within the continuous phase increase the probability of contact with radiation-active species, preventing free radicals from further initiating chain breakage of the polymer backbone; simultaneously, activation of the hafnium-porphyrin metal-organic framework and The pores are loaded and combined with low-molecular-weight diamines to enter the remaining pores and undergo in-situ polycondensation. This avoids the problem that pre-made polymers mainly remain on the outer surface of particles due to their large molecular size and system viscosity. This forms a through-and mechanical interlocking effect between the polyimide inside and outside the pores and the metal-organic framework. The polymer inside the pores provides support for the porous framework, while the rigid framework restricts the polymer chain segments from sliding under continuous pressure, reducing the tendency for compression creep, interfacial debonding, and microcrack formation.
[0018] 2. The tetra(4-carboxyphenyl)porphyrin ligand of this invention exhibits aromatic conjugated interfacial affinity with aromatic polyimides, which improves polymer wetting of particle surfaces and reduces interfacial porosity and thermal resistance and stress concentration caused by voids. The segmented imidization process allows for the gradual removal of solvent and cyclized water, reducing closed-cell, bubbling, and internal defects caused by rapid heating. Furthermore, 2,5-diaminopyridine retains pyridine nitrogen while participating in the formation of the polyimide backbone. Pyridine nitrogen can form Lewis acid-base coordination links with open Hf coordination sites. The final imidization stage applies hot pressure, which shortens the interfacial distance between the polymer and the metal-organic framework, promotes the approach of coordination sites, and compresses the residual free volume, resulting in a denser interfacial load transfer path between the particles and the continuous polyimide phase compared to ordinary physical blends.
[0019] 3. This invention limits the particle size, mesopore size, and open Hf coordination sites of the metal-organic framework particles. The loading amount, diamine composition, monomer stoichiometry, and hot pressing window are used to balance interfacial coordination, pore filling, framework stability, and material density, thereby improving the consistency of material preparation and making the resulting material suitable for the preparation of seals in the high-temperature and high-pressure fluid environment of nuclear reactors. Attached Figure Description
[0020] The accompanying drawings, which are included to provide a further understanding of embodiments of the invention and form part of this application, do not constitute a limitation thereof. In the drawings:
[0021] Figure 1 This is a scanning electron microscope image of hafnium-porphyrin metal-organic framework particles provided in Embodiment 1 of the present invention.
[0022] Figure 2 The fullerene-loaded material provided in Embodiment 1 of the present invention Scanning electron microscope image of hafnium-porphyrin metal-organic framework particles Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0024] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. The terms “comprising,” “including,” “having,” “containing,” etc., as used herein are open-ended, meaning they include but are not limited to. Unless the context clearly indicates otherwise, the expressions “a” and “an” as used herein include plural references. It should be noted that “first,” “second,” etc., are used merely for convenience of description and distinction and should not be construed as indicating or implying relative importance. The term “about” as used herein indicates a range of ±20% of the following numerical value. In some embodiments, the term “about” indicates a range of ±10% of the following numerical value. In some embodiments, the term “about” indicates a range of ±5% of the following numerical value.
[0025] It should be noted that the hafnium-porphyrin metal-organic framework particles referred to in this application are those containing... A porous crystalline material composed of hafnium oxide cluster nodes coordinated with tetra(4-carboxyphenyl)porphyrin ligands, which has the potential to be used for fullerenes. The PCN-222 porphyrin-like metal-organic framework possesses nanoscale pores and can accommodate mesoporous channels into which the polyimide precursor enters, and forms open Hf coordination sites that can coordinate with pyridine nitrogen through defect regulation. Guest molecules; but there are already The research in @PCN-222 primarily utilizes photogenerated charge transfer and cannot directly prove its applicability in high-temperature, high-pressure, and nuclear-irradiated sealing materials; this application is not simply... @MOF is added to polyimide, but by controlling The pre-confinement of pores, subsequent in-pore entry of polyimide precursors, interfacial coordination of pyridine structural units with open Hf sites, and final stage of pressurized imidization result in a composite structure with a defined spatial order. Figure 1 A scanning electron microscope image of hafnium-porphyrin metal-organic framework particles in this embodiment is shown.
[0026] Understandably, fullerenes It can exhibit free radical trapping and electron acceptor properties, however, It may also participate in the generation of reactive oxygen species under aerobic, light-exposed, or specific excitation conditions; therefore, it cannot be generalized to mean that... To ensure its antioxidant effect in any environment, its actual function in the sealed environment of the target nuclear reactor should be confirmed through controlled experiments in light-free, inert atmospheres, deoxygenated high-temperature water, and oxygen-containing environments. Hafnium possesses high photon interaction capability and also strong neutron absorption characteristics; therefore, the radiation resistance mechanism of this application should not be described as simply relying on hafnium nodes to achieve macroscopic radiation shielding, but should be understood as: the hafnium nodes alter the local energy deposition and secondary electron generation environment of the composite material, and the porphyrin conjugated structure and The aromatic polyimide provides delocalization, capture, or termination pathways for the generated excited-state electrons and free radicals, while maintaining a continuous supporting phase. Excessive hafnium content may also increase neutron absorption, local energy deposition, and material brittleness. Therefore, it is necessary to limit the content of hafnium-porphyrin metal-organic framework particles to the range specified in the claims. Figure 2 The fullerene loaded in this embodiment is shown. Scanning electron microscope image of hafnium-porphyrin metal-organic framework particles.
[0027] In addition, the high-temperature and high-pressure water environment in this application can refer to the typical operating conditions of approximately 300°C and 15.5 MPa in the primary loop of a pressurized water reactor. However, due to the different reactor types, sealing locations, and water chemistry regimes, the boric acid, lithium ion, dissolved hydrogen, dissolved oxygen, and irradiation dose rate should be adjusted according to the specific application location during formal implementation.
[0028] Unless otherwise stated, the following examples use the following raw materials:
[0029] Hafnium tetrachloride, purity not less than 99.9 wt%, stored in a desiccator before use; tetra(4-carboxyphenyl)porphyrin, abbreviated as TCPP, purity not less than 98 wt%; benzoic acid, purity not less than 99.5 wt%; fullerene. The following substances are used: 1. Purity not less than 99.9 wt%; 2. Purity not less than 99.5 wt%; 3. Biphenyltetracarboxylic dianhydride (BPDA), dried at 150℃ and 100 Pa absolute pressure for 8 h before use; 3. Phenylenediamine (PDA), purified by vacuum sublimation or recrystallization before use; 4. 2,5-Diaminopyridine (DAP), dried at 80℃ and 100 Pa absolute pressure for 8 h before use; 5. DMF; 6. DMF; 7. DMF; 8. DMF; 9. Methylpyrrolidone; 1. NMP; 1. o-Dichlorobenzene and chlorobenzene, with a moisture content not exceeding 300 mg / kg; 7. Nitrogen or argon, with a purity not less than 99.999 vol% and an oxygen content not exceeding 10 μL / L.
[0030] In addition, in this embodiment, the solid content of the composite polyamic acid system is calculated using the following formula:
[0031] ,
[0032] In the formula, C 60 The mass of the channel-supported hafnium-porphyrin metal-organic framework particles. When the dianhydride and diamine are not completely equimolar, the theoretical mass of the polyimide is calculated by subtracting the theoretical cyclization and dehydration mass from the total mass of the added dianhydride and diamine.
[0033] ,
[0034] In the formula, This is the smaller of the amount of BPDA and the total amount of diamine, expressed in mol. This calculation is used to determine... The weight parts of the channel-loaded MOF relative to the theoretical polyimide.
[0035] Example 1
[0036] This embodiment discloses a general method for preparing hafnium-porphyrin metal-organic framework particles. It includes:
[0037] Step 1: Add hafnium tetrachloride, benzoic acid, and a specified amount of deionized water to DMF and stir until a homogeneous system is formed. Separately, disperse TCPP in DMF and sonicate for 20 min. Slowly add the TCPP dispersion to the system containing hafnium tetrachloride and benzoic acid, and continue sonicating for 20 min.
[0038] Step 2: Transfer the resulting mixture to a pressure-resistant reaction vessel with a polytetrafluoroethylene liner and react at the specified temperature for the specified time. After the reaction is complete, allow it to cool naturally to room temperature and separate the solids by centrifugation at 8000 r / min for 10 min.
[0039] Step 3: Redisperse the solid at a ratio of 20 mL DMF per gram of wet solid, stir at 80°C for 4 h, and then centrifuge; repeat the DMF washing 3 times. Subsequently, perform solvent exchange at a ratio of 20 mL methanol per gram of wet solid, replacing the methanol every 12 h until the specified total exchange time is reached.
[0040] Step 4: After solvent exchange, the solid is pre-dried at 60°C and 5 kPa absolute pressure for 6 h, and then finally activated according to the activation conditions specified in different embodiments.
[0041] The prepared MOF batches must undergo PXRD, nitrogen adsorption-desorption, particle size analysis, and quantification of open Hf sites. Only batches that meet the release range of the corresponding examples can be used for subsequent preparations.
[0042] Tables 1 and 2 below are two parameter tables for MOF preparation batches. In the two tables below, each batch uses 0.500 mmol TCPP, or 0.3954 g TCPP, as a basic reaction unit. When a larger amount is required, it can be scaled up proportionally or multiple parallel batches can be combined.
[0043] Table 1. MOF Preparation Batch Table-1
[0044]
[0045] Table 2. MOF Preparation Batch Table - 2
[0046]
[0047] It should be noted that if the particle size distribution of the same synthesis batch cannot directly meet the requirements of the corresponding embodiment, centrifugal classification can be used, but the target particle size must not be obtained by high-energy ball milling, which would damage the MOF crystal phase. The prepared MOF can be dispersed in anhydrous ethanol at 1.0 g / L and treated with an ultrasonic device with a power of 100 W for 5 min; different particle size fractions can be collected by adjusting the centrifugation speed and time; the classified particles are washed again with methanol and activated under the conditions specified in the corresponding embodiment.
[0048] Example 2
[0049] This embodiment discloses a method for preparing a polymer material that is radiation-resistant, high-temperature resistant, and high-pressure resistant. In this embodiment, 5.584 g of hafnium-porphyrin metal-organic framework particles from batch M1 of Example 1 were taken. This batch should meet the following release conditions:
[0050] The median particle size D50 is 180 nm; the mesopore size is 3.4 nm; the content of open Hf coordination sites is [0.35~0.50mmol / g; the main characteristic peak of PXRD is consistent with the predetermined PCN-222 type hafnium-porphyrin framework.
[0051] Step 1: Activation of hafnium-porphyrin metal-organic framework particles; The selected hafnium-porphyrin metal-organic framework particles were placed in a vacuum desiccator and activated at 150℃ and 100 Pa absolute pressure for 12 h; After activation, the particles were cooled to room temperature under dry nitrogen protection to avoid prolonged contact with moisture in the air.
[0052] Step 2: Channel load; weigh 0.279 g of A 2.0 g / L solution with o-dichlorobenzene was prepared, with a solution volume of 139.5 mL; the activated hafnium-porphyrin metal-organic framework particles were then added. The solution was stirred at 40℃ and 300 r / min, and four depressurization-repressurization cycles were performed. The effects of each cycle were as follows:
[0053] Reduce the system pressure to 15 kPa absolute pressure within 5 minutes and maintain it for 30 minutes;
[0054] Dry nitrogen gas was introduced within 5 minutes to restore the pressure to atmospheric pressure, and the pressure was maintained at atmospheric pressure for 15 minutes.
[0055] After completing 4 cycles, continue soaking at 40°C for 12 hours.
[0056] Separate the solid by centrifugation at 6000 r / min for 10 min, and first wash twice with 15 mL of o-dichlorobenzene each time, with each shaking time not exceeding 2 min, to remove outer surface crystals or weak adsorption. Wash three times with 30 mL of anhydrous methanol each time to replace o-dichlorobenzene.
[0057] The obtained particles were dried at 110°C and 100 Pa absolute pressure for 8 h to obtain approximately 5.864 g. Pore-loaded hafnium-porphyrin metal-organic framework particles.
[0058] Step 3: In-situ formation of polyamic acid; Weigh 9.192 g of PDA, i.e. 0.085 mol; Weigh 1.637 g of DAP, i.e. 0.015 mol, with a molar ratio of PDA to DAP of 85:15.
[0059] PDA and DAP were added to pre-dried DMAc, with a total DMAc content of 184.458 g and a moisture content controlled to be no more than 200 mg / kg.
[0060] Stirring under nitrogen atmosphere until the diamine is completely dissolved, then add the mixture prepared in step 2. Pore-supported hafnium-porphyrin metal-organic framework particles were dispersed at 1000 r / min for 40 min.
[0061] The system temperature was controlled at 10℃, and three decompression-recompression cycles were performed. Each time, the pressure was reduced to 15 kPa absolute pressure and held for 20 min, and then restored to normal pressure and held for 10 min, so that the diamine solution could enter the remaining pores of the hafnium-porphyrin metal-organic framework particles.
[0062] Weigh 29.422 g of BPDA, which is 0.100 mol. Divide the BPDA into 10 equal portions, each approximately 2.942 g. Add one portion to the reaction system every 20 minutes, keeping the system temperature at 10–15 °C during the addition process.
[0063] After all BPDA was added, the system was heated to 20°C and stirred for another 12 hours to obtain a composite polyamic acid system with a solid content of 20 wt%. A small amount of the polyamic acid system was then taken to determine its apparent viscosity and residual anhydride.
[0064] Step 4: Degassing, molding and segmented imidization; Degas the composite polyamic acid system under 10 kPa absolute pressure for 30 min and inject it into a sealing ring mold preheated to 60℃.
[0065] The temperature was increased to 100℃ at 2℃ / min under a nitrogen atmosphere and held for 1.5 h; then increased to 185℃ at 2℃ / min and held for 1.5 h; subsequently increased to 315℃ at 3℃ / min.
[0066] Once the material temperature reaches 280℃, pressure is gradually applied, increasing the pressure to 20 MPa within 20 minutes, and then maintained at 315℃ and 20 MPa for 2 hours.
[0067] Maintain a pressure of 20 MPa, cool to 80°C at a rate not exceeding 3°C / min, release the pressure, and continue cooling to room temperature to obtain the polymer material.
[0068] Step 5: Post-curing and high-temperature high-pressure water pretreatment; the material is post-cured at 345℃ for 2 hours under a nitrogen atmosphere.
[0069] The post-curing material was placed in a high-temperature, high-pressure reactor, and deoxygenated water with a conductivity of no more than 1 μS / cm was added. After purging with nitrogen three times, the temperature was raised to 300℃, and the pressure was maintained at 15.5 MPa for 72 h of pretreatment.
[0070] After pretreatment, the sample was slowly cooled and depressurized, then removed and dried at 180℃ and 200 Pa absolute pressure for 8 h.
[0071] Example 2
[0072] In this embodiment, 2.833 g of hafnium-porphyrin metal-organic framework particles from batch M2 were collected, and the batch release parameters were as follows:
[0073] D50 is 460 nm; mesopore size is 4.0 nm; open Hf site content is 0.15 mmol / g.
[0074] Hafnium-porphyrin metal-organic framework particles were activated at 120 °C and 500 Pa absolute pressure for 6 h.
[0075] Weigh 0.057 g was prepared into a 0.5 g / L solution with chlorobenzene, with a volume of 113.4 mL. The activated hafnium-porphyrin metal-organic framework particles were then added... In the solution, two decompression-recompression cycles were performed at 20℃. Each time, the pressure was reduced to 30 kPa absolute pressure and held for 10 min, then restored to normal pressure. After the cycle was completed, the solution was immersed for another 4 h.
[0076] After separating the solid, it was rapidly washed once with chlorobenzene, then washed three times with methanol, and dried at 80°C and 500 Pa absolute pressure for 4 h to obtain approximately 2.890 g. Pore-loaded hafnium-porphyrin metal-organic framework particles.
[0077] Weigh out 10.273 g of PDA (0.095 mol), 0.546 g of DAP (0.005 mol), and 28.834 g of BPDA (0.098 mol). The molar ratio of BPDA to the total diamine is 0.98:1, and the molar ratio of PDA to DAP is 95:5.
[0078] Dissolve PDA and DAP in 382.880 g of NMP with a water content of no more than 800 mg / kg, and add 2.890 g of [the solution / concentrate]. Pore-supported hafnium-porphyrin metal-organic framework particles were dispersed at 500 r / min for 20 min.
[0079] Two decompression-recompression cycles were performed at 25℃, each time reducing the pressure to 30 kPa absolute pressure and holding it for 10 min.
[0080] BPDA was divided into 6 portions, and one portion was added every 30 minutes. After the addition was completed, the mixture was reacted at 25°C for 6 hours to obtain a composite polyamic acid system with a solid content of 10 wt%.
[0081] After degassing and molding, the temperature was increased to 80℃ at 1℃ / min under a nitrogen atmosphere and held for 0.5 h; then increased to 150℃ and held for 0.5 h; then increased to 260℃, and a pressure of 5 MPa was applied and held for 1 h.
[0082] The pressure was released after cooling to 100°C under 5 MPa pressure.
[0083] Example 3
[0084] In this embodiment, the combined batch of hafnium-porphyrin metal-organic framework particles from batch M3 is 8.466 g, and the batch release parameters are as follows:
[0085] D50 is 100 nm; mesopore size is 3.0 nm; open Hf site content is 0.80 mmol / g.
[0086] The MOF was activated at 180℃ and 50 Pa absolute pressure for 18 h.
[0087] Weigh 0.847 g was prepared into a solution with a concentration of 5.0 g / L and a volume of 169.4 mL using o-dichlorobenzene.
[0088] Hafnium-porphyrin metal-organic framework particles were added to C 60 In the solution, six decompression-recompression cycles were performed at 60℃, with each cycle reducing the pressure to 5 kPa absolute and holding it for 60 min. After the cycle was completed, the solution was left to soak for another 24 h.
[0089] After separation and washing, the sample was dried at 150℃ and 50 Pa absolute pressure for 12 h to obtain approximately 9.313 g. Pore-loaded hafnium-porphyrin metal-organic framework particles.
[0090] Weigh out 7.570 g of PDA (0.070 mol), 3.274 g of DAP (0.030 mol), and 30.010 g of BPDA (0.102 mol). The molar ratio of PDA to DAP is 70:30, and the molar ratio of BPDA to the total amount of diamine is 1.02:1.
[0091] A mixed solvent of DMAc and NMP in a mass ratio of 1:1 was used, with a total mass of 117.056 g and a water content of no more than 100 mg / kg.
[0092] After dissolving the two diamines, 9.313 g was added. Pore-supported hafnium-porphyrin metal-organic framework particles were dispersed at 1500 r / min for 60 min. Five decompression-recompression cycles were performed at −5 °C, each time reducing the pressure to 5 kPa absolute and holding for 40 min.
[0093] BPDA was divided into 20 portions, and one portion was added every 10 minutes, while maintaining the temperature at -5 to 5°C during the addition process. After all the BPDA was added, the system was heated to 25°C and reacted for 24 hours to obtain a composite polyamic acid system with a solid content of 30 wt%.
[0094] After degassing and molding, the temperature is increased to 120℃ at 5℃ / min and held for 2 h; then increased to 220℃ and held for 2 h; then increased to 330℃, and a pressure of 30 MPa is applied and held for 3 h.
[0095] The pressure was released after cooling to 60°C under 30 MPa pressure.
[0096] Example 4
[0097] In this embodiment, 4.254 g of hafnium-porphyrin metal-organic framework particles from batch M4 were taken and activated at 135°C and 300 Pa absolute pressure for 9 h.
[0098] Weigh 0.128 g was prepared into a solution with a concentration of 1.0 g / L and a volume of 127.6 mL using a mixed solvent of o-dichlorobenzene and chlorobenzene in a mass ratio of 1:1.
[0099] Three decompression-recompression cycles were performed at 30℃, each time reducing the pressure to 25 kPa and holding it for 20 min. After each cycle, the solid was impregnated for another 8 h. The solid was then dried at 95℃ and 300 Pa for 6 h to obtain approximately 4.382 g.
[0100] Pore-loaded hafnium-porphyrin metal-organic framework particles.
[0101] Weigh out 9.733 g of PDA (0.090 mol), 1.091 g of DAP (0.010 mol), and 29.275 g of BPDA (0.0995 mol).
[0102] Two diamines were dissolved in 252.056 g of DMAc, and then... Pore-supported hafnium-porphyrin metal-organic framework particles were dispersed at 700 r / min for 30 min. The dispersion was then subjected to three cycles of decompression to 25 kPa absolute pressure and held for 15 min each.
[0103] Divide BPDA into 8 portions and add one portion every 25 minutes at a feeding temperature of 0–10°C. After feeding, react at 15°C for 8 hours.
[0104] After degassing and molding, the temperature was sequentially maintained at 90℃ for 1 h, 170℃ for 1 h, and 300℃ for 1 h; at the 300℃ stage, a pressure of 15 MPa was applied, and the temperature was cooled to 90℃ under pressure.
[0105] Example 5
[0106] Take 6.878 g of hafnium-porphyrin metal-organic framework particles from batch M5 and activate them at 165℃ and 80 Pa absolute pressure for 15 h.
[0107] Weigh 0.481 g was prepared into a 4.0 g / L solution with o-dichlorobenzene, with a volume of 120.3 mL.
[0108] Five decompression-recompression cycles were performed at 50℃, each time reducing the pressure to 10 kPa and holding it for 45 min; after each cycle, the sample was soaked for another 16 h. After separation, the sample was dried at 135℃ and 80 Pa for 10 h to obtain approximately 7.360 g. Pore-loaded hafnium-porphyrin metal-organic framework particles.
[0109] Weigh out 8.651 g of PDA (0.080 mol), 2.183 g of DAP (0.020 mol), and 29.569 g of BPDA (0.1005 mol).
[0110] The diamine was dissolved in 143.289 g of NMP, and then added... Pore-supported hafnium-porphyrin metal-organic framework particles were dispersed at 1200 r / min for 50 min. The dispersion was then subjected to four cycles of decompression to 10 kPa absolute pressure and held for 30 min each.
[0111] The BPDA was divided into 16 portions, and one portion was added every 15 minutes, with the addition temperature controlled at 15°C. After the addition was complete, the mixture was reacted at 25°C for 18 hours.
[0112] After degassing and molding, the temperature was sequentially maintained at 110℃ for 2 h, 200℃ for 2 h, and 325℃ for 2.5 h; a pressure of 25 MPa was applied at the 325℃ stage, and the temperature was cooled to 60℃ under pressure.
[0113] The material was cured in nitrogen at 360°C for 1 h, then pretreated in deoxygenated water at 320°C and 18 MPa for 24 h, and then dried at 200°C and 100 Pa absolute pressure for 6 h.
[0114] Example 6
[0115] 5.286 g of hafnium-porphyrin metal-organic framework particles from batch M6 were taken and activated at 150℃ and 200 Pa absolute pressure for 12 h.
[0116] Weigh 0.211 g was prepared into a 2.5 g / L solution with chlorobenzene, with a volume of 84.6 mL.
[0117] Four decompression-recompression cycles were performed at 35℃, each time reducing the pressure to 20 kPa absolute pressure and holding it for 25 min; after each cycle, the sample was soaked for another 10 h.
[0118] After separating the solid, it was rapidly washed twice with o-dichlorobenzene, then three times with anhydrous methanol, and dried at 120°C and 200 Pa absolute pressure for 8 h to obtain approximately 5.497 g. Pore-supported hafnium-porphyrin metal-organic framework particles F.
[0119] The extractable surface area of the particle should be tested. The proportion should be no greater than 20 wt%; the residual chlorine content should be detected by ion chromatography or combustion ion chromatography and should be no greater than 100 mg / kg.
[0120] Weigh out 9.192 g of PDA, 1.637 g of DAP, and 29.422 g of BPDA. Use a mixed solvent of DMAc and NMP in a mass ratio of 7:3, and the total mass is 162.198 g.
[0121] After dissolving the diamine, add Pore-supported hafnium-porphyrin metal-organic framework particles were dispersed at 900 r / min for 40 min; then subjected to four cycles of decompression to 20 kPa absolute pressure and held for 25 min at 5 °C.
[0122] BPDA was divided into 12 portions, and one portion was added every 20 minutes. After adding the ingredients, the mixture was reacted at 20°C for 15 hours.
[0123] After degassing and molding, the mixture was sequentially held at 100℃ for 1 h, 190℃ for 1 h, and 310℃ for 2 h; at the 310℃ stage, a pressure of 18 MPa was applied, and the mixture was cooled to 75℃ under pressure.
[0124] The material was cured at 340°C for 4 h under a nitrogen atmosphere, then pretreated in deoxygenated water at 280°C and 10 MPa for 168 h, and then dried at 150°C and 1000 Pa absolute pressure for 12 h.
[0125] Example 7
[0126] This embodiment illustrates the scale-up preparation of channel-loaded hafnium-porphyrin metal-organic framework particles.
[0127] Add 20.0 L of DMF, 384.36 g of hafnium tetrachloride (1.200 mol), 5861.76 g of benzoic acid (48.0 mol), and 108.4 mL of deionized water (6.0 mol) to a 30 L stirred jacket reactor.
[0128] Separately, 158.156 g of TCPP, or 0.200 mol, was dispersed in 2.0 L of DMF and ultrasonically or by high-speed shear for 30 min, and then added to the reactor within 1 h.
[0129] The mixture was heated to 120°C under nitrogen protection and reacted for 24 h. After cooling and filtration, it was washed with DMF and exchanged with methanol. After fractionation and activation, particles with a D50 of 180–250 nm, a mesopore size of 3.4–3.8 nm, and an open Hf site concentration of 0.35–0.50 mmol / g were selected.
[0130] Take 167.533 g of it and activate it at 150℃ and 100 Pa absolute pressure for 12 h.
[0131] Weigh 8.377 g was prepared into a 2.0 g / L solution with o-dichlorobenzene, with a volume of 4.188 L.
[0132] Hafnium-porphyrin metal-organic framework particles were added to the solution and subjected to four cycles of decompression to 15 kPa absolute pressure at 40°C and maintained for 30 min. After the cycle, the particles were immersed for another 12 h.
[0133] After filtration, rapid washing, and vacuum drying, 175.909 g was obtained. Pore-loaded hafnium-porphyrin metal-organic framework particles.
[0134] Preparation of kilogram-sized polyamic acid:
[0135] Weigh out 275.757 g of PDA (2.550 mol), 49.108 g of DAP (0.450 mol), and 882.660 g of BPDA (3.000 mol).
[0136] Based on theoretical calculations, the mass of the obtained polyimide is approximately:
[0137]
[0138] PDA and DAP were added to 5533.740 g of DMAc and dissolved under nitrogen protection. 175.909 g of [the solution] was then added. Pore-supported hafnium-porphyrin metal-organic framework particles were dispersed for 40 min in a jacketed reactor with an anchored stirrer and a high-speed disperser.
[0139] The pressure was reduced to 15 kPa absolute pressure three times at 10°C and maintained for 20 min.
[0140] BPDA was divided into 10 portions, each 88.266 g, and added every 20 min. The temperature was controlled at 10–15 °C during the feeding process using a jacket cooling system. After the feeding was completed, the mixture was reacted at 20 °C for 12 h to obtain a composite polyamic acid system with a solid content of 20 wt%.
[0141] Final molding and solvent recovery:
[0142] The polyamic acid system was metered and injected into a multi-cavity sealing mold, and imidization was completed according to the temperature program and molding pressure of 20 MPa in Example 1.
[0143] The DMAc and water vapor discharged during the 80–220℃ stage were collected, condensed, and then subjected to vacuum distillation at 5 kPa absolute pressure and 90–110℃. The distillate was dried through a 3A molecular sieve until the water content was no more than 500 mg / kg.
[0144] Recycled DMAc is used at a rate of 50 wt% of the total mass of the next batch of solvent, with the remaining 50 wt% being fresh DMAc.
[0145] The batches of recycled solvents must be tested for moisture, acid value, amine residue, chloride ions, and non-volatile residues. They can only be recycled if all indicators meet the requirements for polyamic acid preparation.
[0146] Comparative Example 1
[0147] A DAP-free BPDA / PDA polyimide system is used.
[0148] Weigh out 10.814 g of PDA (0.100 mol), 29.422 g of BPDA (0.100 mol), and prepare DMAc according to a 20 wt% solid content.
[0149] First, PDA is dissolved in DMAc, then BPDA is added in 10 portions, and the mixture is reacted at 20°C for 12 hours to form pre-prepared polyamic acid.
[0150] Pore-supported hafnium-porphyrin metal-organic framework particles
[0151] Take another unloaded 5.582 g of M1 type hafnium-porphyrin metal-organic framework particles (hereinafter referred to as MOF) and free 0.279 g of the two were added directly to the already formed polyamic acid and mixed at 1000 r / min for 40 min.
[0152] No depressurization-repressurization cycle is performed to allow diamine to enter the MOF channels, and no further depressurization-repressurization cycle is performed. Pre-loaded channels.
[0153] The same imidization temperature and final hot-pressing conditions of 20 MPa as in Example 1 were used.
[0154] Comparative Example 2
[0155] Except for not performing Apart from the duct load, the rest of the operation is the same as in Example 1.
[0156] Take 5.584 g of M1 type MOF, activate it at 150℃ and 100 Pa absolute pressure for 12 h, and then directly add it to the DMAc solution of PDA and DAP for depressurization-recompression cycling and batch polymerization of BPDA.
[0157] This comparative example retains MOF channel polymerization and Hf-N coordination, but lacks... Used for evaluation Effects on irradiation free radical concentration, post-irradiation strength retention rate, and long-term thermo-oxidative aging.
[0158] Comparative Example 3
[0159] The amount of PDA used was 10.814 g and BPDA was 29.422 g, both with a molar amount of 0.100 mol.
[0160] Using 5.582 g of M1 type MOF and 0.279 g The produced The channel-loaded MOF was subjected to depressurization-repressurization cycles, batch polymerization, and final hot pressing as described in Example 1.
[0161] This comparative example has The pores are confined and polymerized within the pores, but the polyimide does not contain pyridine nitrogen and therefore cannot form the Hf-N coordination interface.
[0162] Comparative example and Comparative example 2 are retained respectively. A key factor in channel confinement and Hf-N coordination can be used in conjunction with Example 1 to evaluate whether the two produce a combined effect that exceeds the individual effects.
[0163] Comparative Example 4
[0164] The raw material composition and dosage are the same as in Example 1.
[0165] PDA, DAP, and BPDA were first reacted in MOF-free DMAc for 12 h to prepare pre-polyamic acid. Then, 5.864 g of [the mixture] was added. The channel-loaded MOF was mixed at 1000 r / min for 40 min.
[0166] The low molecular weight diamine and MOF are not subjected to depressurization-recompression cycling, nor is BPDA stepwise polymerization carried out in the presence of MOF.
[0167] The subsequent imidization and hot-pressing conditions were the same as in Example 1.
[0168] This comparative example is used to demonstrate that even if the components and final hot-pressing conditions are exactly the same, if a high molecular weight polyamic acid is formed first and then added to the MOF, the proportion of the polymer entering the MOF channels may still decrease significantly.
[0169] Comparative Example 5
[0170] In this comparative example The load exceeds the upper limit of the claims.
[0171] remove Except for changing the mass ratio of MOF to 15:100, the rest of the operation is the same as in Example 1.
[0172] Take 5.099 g of M1 type MOF, weigh... 0.765 g yielded a high load of approximately 5.864 g. @MOF, making it the final addition The total mass of the MOF remains the same as in Example 1.
[0173] Using 2.0 g / L The o-dichlorobenzene solution requires a volume of 382.5 mL. After completing the depressurization-repressurization and impregnation, subsequent polymerization and molding are carried out according to Example 1.
[0174] This comparative example is used to verify C. 60 When the / MOF mass ratio exceeds 10:100, does the amount of diamine entering the pores, the proportion of polymerization within the pores, the Hf-N coordination ratio, and the high-pressure creep performance deteriorate due to pore blockage and reduced remaining pore volume?
[0175] Table 3 shows the structural and preparation quality data of the above-mentioned embodiments and comparative examples; Table 4 shows the mechanical, thermal and irradiation performance data of the above-mentioned embodiments and comparative examples (Table 1 and Table 4 show the mechanical, thermal and irradiation performance data of the above-mentioned embodiments and comparative examples (Table 2).
[0176] Table 3. Structure and Preparation Quality Data
[0177]
[0178] Table 4. Mechanical, thermal, and irradiation performance data. Table 1
[0179]
[0180] Table 5. Mechanical, thermal, and irradiation performance data (Table 2)
[0181]
[0182] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A polymeric material for radiation resistance, high temperature resistance, and high pressure resistance, characterized in that, The polymer material is a polyimide-based composite material, comprising: An aromatic polyimide matrix as the continuous phase, and fullerene-supported hafnium-porphyrin metal-organic framework particles dispersed in the aromatic polyimide matrix. The hafnium-porphyrin metal-organic framework particles are porous crystalline materials formed by the coordination of hafnium-oxygen cluster nodes with carboxyl-containing porphyrin ligands. The porous crystalline material has mesoporous channels and open hafnium coordination sites. The fullerene is confined within the mesoporous channels; The aromatic polyimide matrix is a product obtained by imidization reaction of an aromatic dianhydride component and an aromatic diamine component. The aromatic diamine component includes an aromatic diamine containing a pyridine structure. The pyridine nitrogen in the aromatic diamine containing the pyridine structure coordinates with the open hafnium coordination site, thereby forming an interfacial coordination bond between the hafnium-porphyrin metal-organic framework particles and the aromatic polyimide matrix.
2. The polymer material for radiation resistance, high temperature resistance, and high pressure resistance according to claim 1, characterized in that, The hafnium-porphyrin metal-organic framework particles are PCN-222 type metal-organic frameworks, the hafnium oxygen cluster nodes are nodes containing Hf6O4(OH)4 clusters, and the carboxyl-containing porphyrin ligands are tetrakis(4-carboxyphenyl)porphyrin.
3. The polymer material for radiation resistance, high temperature resistance, and high pressure resistance according to claim 1, characterized in that, The hafnium-porphyrin metal-organic framework particles have an open hafnium coordination site content of 0.15~0.80 mmol / g, a mesopore size of 3.0~4.0 nm, and a median particle size D50 of 100~460 nm. The aromatic dianhydride component is 3,3′,4,4′-biphenyltetracarboxylic dianhydride, and the molar ratio of the aromatic dianhydride component to the aromatic diamine component is 0.98:1 to 1.02:
1.
4. The method for preparing a radiation-resistant, high-temperature-resistant, and high-pressure-resistant polymer material according to claim 1, characterized in that, Based on 100 parts by weight of the aromatic polyimide matrix, the content of the fullerene-supported hafnium-porphyrin metal-organic framework particles is 8 to 25 parts by weight, and the proportion of fullerene in the hafnium-porphyrin metal-organic framework particles is 2 to 10 wt%.
5. The method for preparing a radiation-resistant, high-temperature-resistant, and high-pressure-resistant polymer material according to claim 1, characterized in that, The proportion of extractable surface fullerenes in the fullerene-supported hafnium-porphyrin metal-organic framework particles is no more than 20 wt%, and the residual chlorine content is no more than 100 mg / kg.
6. A method for preparing a polymer material that is radiation-resistant, high-temperature resistant, and high-pressure resistant, characterized in that, The polymer material according to any one of claims 1 to 5 is prepared according to the following method: S1. Activate hafnium-porphyrin metal-organic framework particles; S2, Fullerene pore loading: The activated hafnium-porphyrin metal-organic framework particles are added to the fullerene solution, and the fullerene is allowed to enter and be confined in the mesoporous channels through depressurization-repressurization cycling. Then, the particles are separated, washed and dried to obtain fullerene pore-loaded hafnium-porphyrin metal-organic framework particles. S3, In-situ formation of polyamic acid: Aromatic diamine components, including aromatic diamines containing pyridine structures, are dissolved in an organic solvent, added to and dispersed with particles obtained in S2, and the diamine solution is allowed to enter the remaining channels of the mesoporous channels through a depressurization-repressurization cycle. Subsequently, aromatic dianhydride components are added in batches to react and obtain a composite polyamic acid system. S4. Segmented imidization: The composite polyamic acid system is degassed, molded, and imidized by programmed temperature rise. Pressure is applied during the high-temperature stage of imidization, and the pressure is maintained before cooling to obtain the polymer material.
7. The method for preparing a radiation-resistant, high-temperature-resistant, and high-pressure-resistant polymer material according to claim 6, characterized in that, The activation described in S1 is carried out at a temperature of 120~180 ℃ and an absolute pressure of 50~500 Pa. The solvent for the fullerene solution in S2 is o-dichlorobenzene, chlorobenzene, or a mixture of the two, and the number of depressurization-repressurization cycles is 2 to 6.
8. The method for preparing a radiation-resistant, high-temperature-resistant, and high-pressure-resistant polymer material according to claim 6, characterized in that, The highest temperature of imidization in S4 is 260~330 ℃, and the pressure applied in the high-temperature stage is 5~30 MPa.
9. The method for preparing a radiation-resistant, high-temperature-resistant, and high-pressure-resistant polymer material according to claim 6, characterized in that, The preparation method further includes: S5, curing the polymer material obtained in S4 at 340~360 ℃ under an inert atmosphere, then pretreating it in deoxygenated water at 280~320 ℃ and 10~18 MPa, and then drying it.